2007
DOI: 10.1007/s00412-007-0111-y
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Mei4, Rec114, and other proteins required for meiotic DNA double-strand break formation in Saccharomyces cerevisiae

Abstract: In most sexually reproducing organisms, meiotic recombination is initiated by DNA double-strand breaks (DSBs) formed by the Spo11 protein. In budding yeast, nine other proteins are also required for DSB formation, but roles of these proteins and interactions among them are poorly understood. We report here further studies of the behaviors of these proteins. Consistent with other studies, we find that Mei4 and Rec114 bind to chromosomes from leptonema through early pachynema. Both proteins showed only limited c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
204
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(219 citation statements)
references
References 71 publications
14
204
0
1
Order By: Relevance
“…However, in S. cerevisiae, Rec114 phosphorylation decreases DSB activity but does not lead to Rec114 depletion from axes as assayed by chromatin immunoprecipitation. The dynamics of Mei4 localization in S. cerevisiae (Li et al, 2006;Maleki et al, 2007), S. pombe (Lorenz et al, 2006) and the DSB-1 and DSB-2 proteins in C. elegans, which might play similar functions to Mei4 and Rec114 Stamper et al, 2013), share similar properties to those we have described in mice, although differences in the mechanism of regulatory pathways might operate in these species.…”
Section: Discussion Association Of Mei4 With Chromosome Axessupporting
confidence: 73%
“…However, in S. cerevisiae, Rec114 phosphorylation decreases DSB activity but does not lead to Rec114 depletion from axes as assayed by chromatin immunoprecipitation. The dynamics of Mei4 localization in S. cerevisiae (Li et al, 2006;Maleki et al, 2007), S. pombe (Lorenz et al, 2006) and the DSB-1 and DSB-2 proteins in C. elegans, which might play similar functions to Mei4 and Rec114 Stamper et al, 2013), share similar properties to those we have described in mice, although differences in the mechanism of regulatory pathways might operate in these species.…”
Section: Discussion Association Of Mei4 With Chromosome Axessupporting
confidence: 73%
“…Chromatin immunoprecipitation indicated that Spo11 was not present at the ARE1 hotspot in the absence of REC114 (Prieler et al 2005;Sasanuma et al 2008) or phosphorylatable REC107 . Consistent with this, Rec114 and Mei4 were present on chromatin (Maleki et al 2007), and at hotspots (ChIP) in the absence of SPO11 . However, Prieler et al (2005) found that Spo11 binds hotspot DNA in both a rec107D and a mei4D strain.…”
supporting
confidence: 72%
“…Several analyses have demonstrated that three subcomplexes exist among the 10 recombination initiation proteins: the Spo11-subcomplex: Spo11, Ski8, Rec102, and Rec104 (Salem et al 1999;Uetz et al 2000;Kee and Keeney 2002;Jiao et al 2003;Arora et al 2004;Cheng et al 2004;Kee et al 2004); the Rec114-subcomplex: Rec114, Rec107, and Mei4 Henderson et al 2006;Li et al 2006;Maleki et al 2007;Sasanuma et al 2008); and the MRX-subcomplex: Mre11, Rad50, and Xrs2 (Borde 2007). Some data suggest that components from different subcomplexes also interact ); one interpretation is that the 10 proteins form a single holocomplex to create DSBs.…”
mentioning
confidence: 99%
“…Speculations regarding the prominence of up-regulated splicing during yeast meiosis-by transition from a vegetative ''splicing-off'' state to a new ''splicing-on'' modehave focused on its potential to protect vegetative cells from the untimely production of potentially deleterious meiotic proteins (Juneau et al 2007;Maleki et al 2007). Maintenance of the splicing-off state in vegetative cells is, in effect, a back-up to the ''transcription-off'' state of most meiotic intron-containing genes during vegetative growth (Primig et al 2000;Rabitsch et al 2001;Munding et al 2010;Qiu et al 2011a), MER2 being an exception that is transcribed constitutively (but spliced inefficiently) in vegetative cells (Engebrecht et al 1991).…”
Section: Discussionmentioning
confidence: 99%